History of postpartum depression as a contributor to the severity of NAS. (February 2019) - Nellhaus, Emma M.; Nieuwenhuizen, Louis; Egleton, Richard; Hansen, Zachary; Chaffin, David; Loudin, Sean; Davies, Todd H.
Abstract: Currently, there are no clinical tools available to accurately predict the severity of neonatal withdrawal. Studies of non-exposed neonates suggest that maternal depression and anxiety are predictive of negative short and long-term neonatal outcomes, but research is lacking in the addicted population. We studied of 109 pregnant women in medication-assisted treatment (MAT) and their neonates to determine if psychiatric conditions co-occurring with Substance Use Disorder (SUD) contributed to the severity of neonatal withdrawal. The need for pharmacological intervention, Finnegan scores, length of methadone treatment, and length of hospital stay were used to assess withdrawal severity. Categorical variables were analyzed in Stata14 using Chi Square and continuous variables were analyzed using Wilcoxon Rank Sum. Among the 110 neonates whose outcomes were reviewed, a maternal history of Postpartum Depression (PPD) was found to be correlated with increased severity of withdrawal. The neonates born to mothers with past diagnoses of PPD had more consecutive days of high Finnegan scores (95% confidence interval [CI], P  = 0.003), longer length of treatment (95% CI, P  = 0.006), and length of hospital stay (95% CI, P  = 0.014). There was no apparent relationship between NAS severity and other psychiatric disorders. In a study of pregnant women with SUD and their neonates, we uncovered a relationship between the severity of NAS and maternal history of PPD. Our findings demonstrate that further research into these deleterious outcomes is warranted. Until then, we suggest collection of maternal history of PPD and careful screening for new cases in the SUD population. Highlights: Maternal history of Post-Partum Depression correlated to more severe NAS. Prenatally exposed male neonates withdrawal more severely. Neonate NAS was not altered by most maternal co-occurring psychiatric conditions.